Rapamycin Mimics the Incompatibility Reaction in the Fungus Podospora anserina - Dementhon, Karine (American Society for Microbiology, 2003)
In filamentous fungi, a programmed cell death (PCD) reaction occurs when cells of unlike genotype fuse. This reaction is caused by genetic differences at specific loci termed het loci (for heterokaryon incompatibility). Although several het genes have been characterized, the mechanism of this cell death reaction and its relation to PCD in higher eukaryotes remains largely unknown. In Podospora anserina, genes induced during the cell death reaction triggered by the het-R het-V interaction have been identified and termed idi genes. Herein, we describe the functional characterization of one idi gene (idi-1) and explore the connection between incompatibility and the response to nutrient starvation. We show that IDI-1 is a cell wall protein which localizes at the septum during normal growth. We found that induction of idi-1 and of the other known idi genes is not specific of the incompatibility reaction. The idi genes are induced upon nitrogen and carbon starvation and by rapamycin, a specific inhibitor of the TOR kinase pathway. The cytological hallmarks of het-R het-V incompatibility (increased septation, vacuolization, coalescence of lipid droplets, induction of autophagy, and cell death) are also observed during rapamycin treatment. Globally the cytological alterations and modifications in gene expression occurring during the incompatibility reaction are similar to those observed during starvation or rapamycin treatment.